Предмет: Алгебра, автор: Marckus

Упростите выражение:

sqrt(12y)-0,5sqrt(48y)+2sqrt(108y)

(5sqrt(7)-sqrt(63)+sqrt(14))*sqrt(7)

Выполните действие:

(2+sqrt(3))(1-sqrt(3))

(sqrt(14)+2)(2-sqrt(14))

(1-2sqrt(3))^2

Сократите дробь:

5-sqrt(5)/2sqrt(5)

a^2-3/a+sqrt(3)

Ответы

Автор ответа: dtnth
0

sqrt{12y}-0,5sqrt{48y}+2sqrt{108y}=\ sqrt{4*3y}-0,5sqrt{16*3y}+2sqrt{36*3y}=\ sqrt{4}*sqrt{3y}-0,5sqrt{16}*sqrt{3y}+2sqrt{36}*sqrt{3y}=\ 2*sqrt{3y}-0,5*4*sqrt{3y}+2*6*sqrt{3y}=\ (2-2+12)*sqrt{3y}=\ 12sqrt{3y}

 

(5sqrt 7-sqrt {63}+sqrt{14})*sqrt7=\ 5sqrt 7 *sqrt7-sqrt {7*9}*sqrt7+sqrt{2*7}*sqrt7=\ 5*7-3*sqrt {7}*sqrt7+sqrt{2}*sqrt7*sqrt7=\ 35-3*7+7sqrt{2}=\ 35-21+7sqrt{2}=14+7sqrt{2}

 

(2+sqrt{3})(1-sqrt{3})=\ 2-2sqrt{3}+sqrt{3}-3=-1-sqrt{3}

 

(sqrt{14}+2)(2-sqrt{14})=\ 2^2-(sqrt{14})^2=4-14=-10

 

(1-2sqrt{3})^2=1-4sqrt{3}+4*3=13-4sqrt{3}

 

frac{5-sqrt{5}}{2sqrt{5}}=\ frac{sqrt{5}(sqrt{5}-1}{2sqrt{5}}=\ frac{sqrt{5}-1}{2}

 

frac{a^2-3}{a+sqrt{3}}=\ frac{(a+sqrt{3})(a-sqrt{3})}{a+sqrt{3}}=a-sqrt{3}

Похожие вопросы
Предмет: География, автор: gulaselmuratova042
Предмет: Математика, автор: Аноним